Sequential analysis of viral load in a neonate and her mother infected with SARS-CoV-2 - Han, Mi Seon (Clin Infect Dis, 2020)
We report changes in viral load over time in a 27-day old neonate with COVID-19 who presented with fever, cough, and vomiting. SARS-CoV-2 RNA was detected in the nasopharynx, oropharynx, stool, saliva, plasma, and urine. The highest viral RNA copies in nasopharynx decreased over time while viral load in stool remained high.